Molecular characterization of non-subtype C and recombinant HIV-1 viruses from Cape Town, South Africa - Wilkinson, Eduan (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScMedSc (Pathology. Medical Virology))--University of Stellenbosch, 2009.